(untitled) - Franklin, Gene F. (Reading, Mass., 1990)
This is a book about the use of digital computers in the real-time control of dynamic systems such as servomechanisms,chemical processes, and ve-chicles that move over water,land,air,or spaces.
Điều khiển số hệ thống động
Keywords: Digital control systems.,Dynamics; Hệ thống điều khiển